Modelling a Conversational Agent with Complex Emotional Intelligence - Belainine, Billal; Sadat, Fatiha; Lounis, Hakim (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Chatbots or conversational agents have enjoyed great popularity in recent years. They surprisingly perform sensitive tasks in modern societies. However, despite the fact that they offer help, support, and fellowship, there is a task that is not yet mastered: dealing with complex emotions and simulating human sensations. This research aims to design an architecture for an emotional conversation agent for long-text conversations (multi-turns). This agent is intended to work in areas where the analysis of users feelings plays a leading role. This work refers to natural language understanding and response generation.